2018
DOI: 10.1016/j.conctc.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to pediatrician and family practitioner participation in pediatric clinical trials: Findings from the Clinical Trials Transformation Initiative

Abstract: Despite legislation to stimulate pediatric drug development through clinical trials, enrolling children in trials continues to be challenging. Non-investigator (those who have never served as a clinical trial investigator) providers are essential to recruitment of pediatric patients, but little is known regarding the specific barriers that limit pediatric providers from participating in and referring their patients to clinical trials. We conducted an online survey of pediatric providers from a wide variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…Mingus et al for instance, found that patients who were approached by their own physician, who used open-ended questions and addressed more specifically patients' personal concerns, were more likely to participate to a clinical trial [25]. A similar finding was reported in a pediatric study [43]. These findings emphasize that willingness to participate is strongly influenced by trust, confidence and the feeling of familiarity with the different aspects of study content, the latter of which is essential to guarantee informed consent [44].…”
Section: Discussionmentioning
confidence: 63%
“…Mingus et al for instance, found that patients who were approached by their own physician, who used open-ended questions and addressed more specifically patients' personal concerns, were more likely to participate to a clinical trial [25]. A similar finding was reported in a pediatric study [43]. These findings emphasize that willingness to participate is strongly influenced by trust, confidence and the feeling of familiarity with the different aspects of study content, the latter of which is essential to guarantee informed consent [44].…”
Section: Discussionmentioning
confidence: 63%
“…Despite several initiatives to stimulate pediatric clinical trial initiation and conduct, the proportion of pediatric trials is 9% [ 1 ], even though children are the recipient of 25% of the global disease burden [ 2 ]. Recruitment and ethical barriers are often cited as a cause by investigators, while fear for invasive measurements and logistical difficulties, such as school schedules for children and demanding jobs for parents are burdens on the participant’s side [ 3 ]. However, the improvement of wireless and portable technology may allow decentralized trials by using health devices in a home-setting.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, clinicians are often not willing to participate in clinical trials due to many related complexities and burdens. In a survey conducted among American pediatricians, the training of the site staff in clinical research procedures resulted as one of the main barriers for participating in a trial [4]. Moreover, lack of time due to daily clinical care is also regularly reported as a signi cant obstacle restraining physicians from participating in clinical research [5,6].…”
Section: Main Textmentioning
confidence: 99%